Re-establishment of Begonia corallina Carrière (Begoniaceae) based on morphoanatomical evidence - Jacques, Eliane De Lima; Ribeiro, Maria Alice Martins; Tozin, Luiz Ricardo Dos Santos (Phytotaxa, 2023)
Begonia corallina Carrière (Begoniaceae) has recently been recognized as synonym of B. maculata Raddi. We show that it is readily distinguished from this species mainly by its coral-red inflorescence, flowers and immature fruits, broadly ovate outer tepals of the staminate flowers and cordiform capsules. Additionally, anatomical investigation highlights further differences, mainly between the leaf blades, such as glandular trichome distribution, palisade parenchyma and midrib thickness, number of vascular bundles on the midrib and sclereid distribution. Accordingly, based on the morphoanatomical differences described here, Begonia corallina Carrière is re-established at the rank of species, and we provide photographs and an emended description of this taxon.